Pemberian Pembebasan Bersyarat Bagi Narapidana Residivis di Lapas Kelas IIA Kota Gorontalo - Abubakar Sidik Mohamad; Dian Ekawaty Ismail; Mohamad Taufiq Zulfikar Sarson (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The implementation of Parole is part of the guidance efforts based on the request of the convict, by considering the provisions of "Law Number 22 of 2022 concerning Corrections, and Government Regulation Number 31 of 1999 concerning Guidance and Guidance of Correctional Inmates, as well as several other implementing regulations. Parole is one of the objectives of the prisoner guidance system which is implemented based on the Correctional system. The goal is to prepare prisoners to be able to integrate with society in a healthy way and return to their role as free and responsible members of society. This process is subject to regulations such as the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 03 of 2018 concerning the Requirements and Procedures for Granting Remission, Assimilation, Visiting Family Leave, Parole, Leave Before Release, and Conditional Leave. This study aims to analyze the implementation of granting parole to recidivist prisoners in the Class IIA Correctional Institution (Lapas) of Gorontalo City. This study uses a normative-empirical research type in the non-judicial case study category, namely a case study conducted without any conflict, so it does not involve the court. The results of the study indicate that the process of granting parole for recidivist prisoners in Class IIA Penitentiary in Gorontalo City is still faced with various obstacles, including the lack of effective guidance, weak supervision, and inconsistent policies. In addition, there is a negative perception from the community towards granting parole to recidivists, which has an impact on their social reintegration. Based on these findings, it is necessary to review policies and improve guidance and supervision programs for recidivist prisoners to reduce the rate of recidivism and increase the effectiveness of parole as a tool for social reintegration.